1972
DOI: 10.1042/bj1260823
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of phospholipids between brain membranes in vitro

Abstract: 1. When unlabelled mitochondria from guinea-pig brain were incubated with a (32)P-labelled microsomal fraction from brain there was a transfer of phospholipid to the mitochondria, which could not be accounted for by an aggregation of microsomes and mitochondria or an exchange with microsomes contaminating the mitochondria. Under similar circumstances there was a transfer of phospholipid from (32)P-labelled mitochondria to microsomes, indicating that the process was one of exchange. 2. The transfer from microso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1972
1972
1978
1978

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…Miller and Dawson [79] observed a transfer of 32p-labelled phospholipids from 32p-labelled guinea pig brain microsomes to unlabelled brain mitochondria in the presence of a brain supernatant. In this study it was shown that the extent of exchange varied with the subcellular membrane particles present in the medium.…”
Section: Exchange Of Phospholipids and The 105 000 X G Supernatantmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller and Dawson [79] observed a transfer of 32p-labelled phospholipids from 32p-labelled guinea pig brain microsomes to unlabelled brain mitochondria in the presence of a brain supernatant. In this study it was shown that the extent of exchange varied with the subcellular membrane particles present in the medium.…”
Section: Exchange Of Phospholipids and The 105 000 X G Supernatantmentioning
confidence: 99%
“…SOME PROPERTIES OF THE pH 5.1 SUPERNATANT FRACTION Phospholipid-exchange activity has been demonstrated in the cell supernatant of a wide variety of tissues such as rat [55,56,66], guinea pig [41] and beef liver [83]; rat [85 ], guinea pig [79 ] and beef brain [86]; rat [85 ] and beef heart [87 ]; rat kidney [85]; and pig thyroid [80]. Exchange activity was not detected in plasma of rat [41] and squirrel monkey [84].…”
Section: Exchange Of Phospholipids and The 105 000 X G Supernatantmentioning
confidence: 99%
“…This conclusion is supported by the isolation, from a liver soluble fraction which catalyses exchange of several lipids, of a protein which catalyses exchange only of phosphatidylcholine [83] . In such experiments with isolated subcellular fractions, the exchange of phosphatidylinositol was rapid in comparison to that of other phospholipids [81] and phosphatidic acid exchange was comparable to that of other lipids [84].…”
Section: Models Based On a Function For A Water-soluble Product Resulmentioning
confidence: 99%
“…By using liver (Wirtz & Zilversmit, 1968;McMurray &Dawson, 1969)and brain (Miller &Dawson, 1972b) subfractions, a transfer of phospholipids between microsomal and mitochondrial fractions and also between a brain supernatant fraction and subsynaptosomal fractions (Miller & Dawson, 1972b) has been demonstrated in vitro. Miller & Dawson (1972a) also demonstrated the ability of synaptic vesicles to synthesize phosphatidylcholine from CDP-choline and sn-1,2-diacylglycerol.…”
Section: Discussionmentioning
confidence: 99%